Preferences for Long-Acting Pre-Exposure Prophylaxis (PrEP), Daily Oral PrEP, or Condoms for HIV Prevention among U.S. Men Who Have Sex with Men - Greene, George J. (AIDS Behav, 2017)
HIV prevention method preferences were evaluated among 512 U.S. men who have sex with men (MSM; median age: 22 years). Approximately 90% consistently preferred one option across pairwise comparisons of condoms, daily oral pre-exposure prophylaxis (PrEP), and long-acting PrEP delivered via either an injectable or one of two types of PrEP implants differing in visibility. Condoms were most frequently preferred (33.8%), followed by non-visible implants (21.5%), and oral PrEP (17.0%); HIV risk was reported by more choosing implants. In a follow-up question comparing the four PrEP options only, daily oral pills and non-visible implants were most frequently preferred (35.5% and 34.3%, respectively), followed by injections (25.2%) and visible implants (4.3%). An inductive, open-coding approach determined that convenience, duration of protection, and privacy were the most commonly cited reasons for a PrEP method choice, and associated with self-report of HIV risk. Tailoring PrEP product development to privacy and other concerns important to those at highest HIV risk may improve HIV prevention.